Development of embedded fuzzy control using reconfigurable FPGA technology - Ayman A. Nada; Mona A. Bayoumi (Automatika, 2024)
The purpose of this work is to investigate the construction of fuzzy embedded control systems combining fast execution and parallel processing capabilities provided by Field Programmable Gate Arrays (FPGAs) and Reconfigurable Inputs/Outputs (RIO) chips. A fixed-point fuzzy controller is developed and implemented on a fast mechatronic system with high-speed control and high channel count on an FPGA target. This paper provides a brief introduction to deploying Fuzzy Logic Control (FLC) methods using RIO-FPGA technology. It suggests a technique for implementing the three stages that constitute the FLC and the PD-like FLC and PID-like FLC structures into practice. Controllers with 1 and 2 degrees of freedom are developed and tested experimentally. Parallel loops, key challenging advantage of LabVIEW programming, are utilized for decoding feedback signals, generating pulse trains for actuator's drivers and for calculation of control gains. An NI-SbRIO board that combines deployable devices with a real-time processor, a re-configurable FPGA, and analogue and digital input–output ports is used. The experimental work demonstrates the significant enhancement of implementing reconfigurable embedded fuzzy control upon such mechatronic systems.